Michael Collins [videorecording] - Jordan, Neil; Woolley, Stephen (Geffen Pictures, 1996)
A story of a man who is a hero whose fighting tactics became a model for other 20th century struggles. A stateman who negotiated Ireland's break with England, a political martyr slain for the great cause he lived and breath.